THU0503 PLUTO TRIAL: SENSITIVITY ANALYSES OF SRI4 RESPONSE WITH BELIMUMAB VS PLACEBO IN PAEDIATRIC PATIENTS WITH CHILDHOOD-ONSET SYSTEMIC LUPUS ERYTHEMATOSUS (CSLE). (2nd June 2020) - Ruperto, N.; Brunner, H.; Mori, M.; Clinch, J.; Syed, R.; Iwata, N.; Bass, D.; Ji, B.; Hammer, A.; Okily, M.; Eriksson, G.; Quasny, H.
Abstract : Background: Belimumab (BEL) is the first treatment approved in children ≥5 years of age with cSLE. This recent approval was based on favourable results of the PLUTO trial, evaluating efficacy and safety of intravenous (IV) BEL, plus standard SLE therapy (SST), vs placebo (PBO), in children with cSLE. 1 Objectives: To evaluate the SLE Responder Index 4 (SRI4) sensitivity of response for the comparison of BEL vs PBO at Week (Wk) 52. Methods: In PLUTO (NCT01649765 ; GSK study BEL114055), an ongoing Phase 2, randomised, PBO-controlled, double-blind study, patients (pts) 5–17 years of age with active cSLE were randomised to monthly BEL 10 mg/kg IV, or PBO, plus SST, for 52 weeks. The primary efficacy endpoint was the SRI4 response rate at Wk 52. Pre-specified sensitivity analyses supporting the primary efficacy endpoint for the intention-to-treat (ITT) population included unadjusted, last observation carried forward (LOCF), completer responses, and response using SLE Disease Activity Index (SLEDAI) 2K proteinuria scoring rule (4-point score for proteinuria >0.5 g/24 h), all at Wk 52. Completers were pts who completed 52 weeks of treatment. Any pts who withdrew or received protocol-prohibited medication or a dose of allowable medication that resulted in treatment failure prior to the Wk 52 visit had missing data handled using LOCF (missing values imputed using the last previous non-missing value). Statistics are descriptive. Results: Overall, 93 pts were randomised (BEL, n=53; PBO, n=40). Majority (94.6%) of pts were female, mean (standard deviation [SD]) age was 14.0 (2.49) years and mean (SD) disease duration was 2.4 (1.93) years. By Wk 52, numerically more BEL (52.8%) than PBO (43.6%) pts were SRI4 responders; difference vs PBO 9.24; odds ratio (OR; 95% confidence interval [CI]) vs PBO 1.49 (0.64, 3.46). For each sensitivity analysis (unadjusted, LOCF, completer, and SLEDAI 2K responses) the odds of being a responder at Wk 52 were higher for pts receiving BEL vs PBO (Table ). Conclusion: The results of the SRI4 primary efficacy endpoint sensitivity analyses further support a favourable effect for BEL vs PBO. References: [1]Brunner HI, et al . Arthritis Rheumatol. 2018;70(59): 3224–5, Abst. 2867 Acknowledgments: We acknowledge all PLUTO investigators (PRINTO, PRCSG and otherwise affiliated). Study funding: GSK. Disclosure of Interests: Nicolino Ruperto Consultant of: Ablynx, AbbVie, AstraZeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GSK, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, Sanofi, Servier, Sinergie, Sobi and Takeda, Hermine Brunner Consultant of: Hoffman-La Roche, Novartis, Pfizer, Sanofi Aventis, Merck Serono, AbbVie, Amgen, Alter, AstraZeneca, Baxalta Biosimilars, Biogen Idec, Boehringer, Bristol-Myers Squibb, Celgene, EMD Serono, Janssen, MedImmune, Novartis, Pfizer, and UCB Biosciences, Speakers bureau: GSK, Roche, and Novartis, Masaaki Mori Grant/research support from: Abbvie Japan, Asahikasei Pharmaceutical, Ayumi Pharmaceutical, CSL Behring, Chugai Pharmaceutical, Japan Blood Products Organization, MSD K.K., Nippon Kayaku, UCB Japan, Consultant of: Daiichi Sankyo, Taisho Pharmaceutical, Jacqueline Clinch Consultant of: Alexion, Speakers bureau: Alexion, Reema Syed: None declared, Naomi Iwata Speakers bureau: Sanofi K.K, Damon Bass Shareholder of: GSK, Employee of: GSK, Beulah Ji Shareholder of: GSK, Employee of: GSK, Anne Hammer Shareholder of: GSK, Employee of: GSK, Mohamed Okily Shareholder of: GSK, Employee of: GSK, Gina Eriksson Shareholder of: GSK, Employee of: GSK, Holly Quasny Shareholder of: GSK, Employee of: GSK